MicroRNA-663a is downregulated in non-small cell lung cancer and inhibits proliferation and invasion by targeting JunD. Issue 1 (December 2016) - Zhang, Yi; Xu, Xiaoman; Zhang, Meng; Wang, Xin; Bai, Xue; Li, Hui; Kan, Liang; Zhou, Yong; Niu, Huiyan; He, Ping
Abstract Background MicroRNA-663a expression is downregulated in several tumors. However, its functions and mechanisms in human non-small cell lung (NSCLC) cancer remain obscure. The present study aimed to identify the expression pattern, biological roles and potential mechanisms by which miR-663a dysregulation is associated with NSCLC. Methods We examined expression level of miR-663a in 62 cases of NSCLC tissues and 5 NSCLC cell lines by reverse transcription PCR. In vitro, gain-of-function and loss-of-function experiments were performed to examine the impact of miR-663a on proliferation, cell cycle progression and invasion of NSCLC cells. Using fluorescence reporter assays, we also explored the potential targets and possible mechanisms of miR-663a in NSCLC cells. Results Downregulation of miR-663a was observed in 42 of 62 of lung cancer tissues compared with paired normal tissues (mean cancer/normal value = 0.745) and its downregulation correlated with nodal metastasis. Transfection of miR-663a mimic suppressed cell proliferation, cell cycle progression and invasion, with downregulation of cyclin D1, cyclin E and MMP9 in both H460 and H1299 cell lines. Transfection of miR-663a inhibitor in both H460 and H1299 cell lines exhibited the opposite effects. In addition, we confirmed that miR-663a could inhibit AP-1 activity and AP-1 component JunD was a direct target of miR-663a in lung cancer cells. Transfection of miR-663a mimic downregulated JunD expression. In addition, JunD siRNA treatment abrogated miR-663a inhibitor-induced expression of cyclin D1, cyclin E and MMP9. Above all, both miRNA mimic and inhibitor in two different NSCLC cell lines demonstrated that miR-663a inhibits proliferation and invasion by targeting AP-1 transcription factor JunD. Conclusions This study indicates that miR-663a downregulation might be associated with NSCLC progression. MiR-663a suppresses proliferation and invasion by targeting AP-1 component JunD in NSCLC cells.